MEMBACA TAFSIR HERMENEUTIKA OTORITAS KHALED ABOU EL FADL - Muslim Zainuddin (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2019)
This paper aims to explain Khaled's thoughts on authority. The emergence of an authoritarian attitude in understanding religious texts is a result of the authority one has in placing a single meaning of a text. This attitude is due to the stagnation of the dialogical relationship between the text, the author and the reader in the realm of Islamic thought. Khaled offers an effort to re-examine the competence of a text, determine the meaning of the text and the attitude of the text reader in expressing the meaning behind the text so that it is in line with the intent of the author of the text. Apart from that, he also offers five requirements that must exist for readers of the text, honesty, sincerity, rationality, thoroughness and self-control.